Analysis of Proton Conducting SOFC–Micro Gas Turbine Hybrid System with Anode and Cathode Recycling and Fueled by Ethanol - Sasmoko, Sasmoko; Tseng, Chung-Jen; Wijayanti, Widya (Jurnal Rekayasa Mesin, 2016)
This paper presents a hybrid system that consists of a pSOFC (proton conducting SOFC) stack, a micro gas turbine (MGT), a combustor, a compressor, a heat exchanger, and an external steam reformer. This simulation is based on thermodynamic analysis and is developed using Matlab/Simulink/Thermolib software and validated using published data from the literature. Furthermore, three cases, cases 1, 2, and 3, are analyzed, and the best case, case 2, is installed with anode and cathode recycling, to increase system performance. According to the results, case 2 exhibits the highest system efficiency (72%) due to high hydrogen production, and the installation of anode and cathode recycling further increases system efficiency up to 79%.